The type of pathogen is associated with organ failure and legacy dysfunction in patients with sepsis - Gao, Qinfen; Li, Zengzheng; Geng, Jiawei; Han, Bin; Yang, Tonghua; Feng, Shuai; Zhao, Lijuan; Teng, Yajun; Li, Yafei; Zhao, Renbin; Zhang, Wei; Wang, Yi; et al. (Frontiers in Immunology, 2025)
IntroductionIs there a difference in pathogen infection among sepsis patients with different organ dysfunction and Post-sepsis persistent organ dysfunction? Is this related to survival? It is currently unclear.MethodsThis study reviewed 1982 sepsis patients between December 2019 and September 2023, and included 619 patients after removing patients with missing data. Of these, 332 were tested for metagenomic next-generation sequencing (mNGS). First, the pathogens distribution was assessed in all NGS-positive patients, followed by patients with different organ dysfunction (excluding those who died during hospitalization). Lastly, the survival analysis was conducted on patients infected with different pathogens.ResultsThe results showed that the mortality rate in our cohort was 27.63% in patients with sepsis, and patients with Respiratory, Liver, Circulatory, Hematologic, Neurological, and Renal dysfunction had poor survival. And patients with post-sepsis persistent organ dysfunction after sepsis have worse survival rates. In addition, we found the infection rates of Legionella and Betapapillomavirus were higher in patients with liver dysfunction. The infection rates of Mastadenovirus, Enterococcus, and Candida were higher in patients with neurological dysfunction. The infection rates of Candida were higher in patients with renal dysfunction and hematologic dysfunction. The infection rates of Moraxella were higher in patients with circulatory dysfunction. The infection rates of Enterococcus, Pneumocystis, and Acinetobacter were higher in patients with Post-sepsis cardiac dysfunction.The infection rates of Enterococcus, Acinetobacter, and Morganella were higher in patients with Post-sepsis liver dysfunction. The infection rates of Enterococcus, Acinetobacter, and Staphylococcus were higher in patients with Post-sepsis respiratory dysfunction. The infection rates of Enterococcus, Candida, Pneumocystis, Staphylococcus, and Listeria were higher in patients with Post-sepsis renal dysfunction. In addition, we found that patients with Escherichia infection in sepsis had the lowest survival rate. The survival rate of patients with Enterococcus infection combined with post-sepsis persistent respiratory dysfunction is also worse.DiscussionIn conclusion, there are differences in the types and proportions of pathogens infected in patients with different organ dysfunction and Post-sepsis persistent organ dysfunction. The combination of Escherichia infection and Enterococcus infection with post-sepsis persistent respiratory dysfunction can affect the survival of patients. We should strengthen the management of sepsis patients, especially those with Post-sepsis persistent organ dysfunction.